2012
DOI: 10.1002/pon.3086
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive features 10 or more years after successful breast cancer survival: comparisons across types of cancer interventions

Abstract: The present study examined the long-term cognitive implications of cancer treatment among breast cancer survivors aged 65 years and older. Fifty-seven women survivors were compared to 30 healthy older female adult comparisons, matched in terms of age and education, with no history of cancer. Cancer survivors were also compared based on treatment intervention, involving chemotherapy (n = 27) versus local therapy through surgery and radiation (n = 30). As a group, the breast cancer survivors scored lower on meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 26 publications
5
55
0
1
Order By: Relevance
“…A participant must be able to quickly compare and process the code box and blank boxes (processing speed), focus on this task for 120 seconds (attention), recall the corresponding symbol (memory), and quickly shift between pairs (executive function) [29]. Several epidemiologic studies have reported cancer patients performing worse on neuropsychological tests for these domains compared to healthy participants [27,28]. Thus, the DSST served as our primary outcome measuring cognitive function.…”
Section: Methodsmentioning
confidence: 99%
“…A participant must be able to quickly compare and process the code box and blank boxes (processing speed), focus on this task for 120 seconds (attention), recall the corresponding symbol (memory), and quickly shift between pairs (executive function) [29]. Several epidemiologic studies have reported cancer patients performing worse on neuropsychological tests for these domains compared to healthy participants [27,28]. Thus, the DSST served as our primary outcome measuring cognitive function.…”
Section: Methodsmentioning
confidence: 99%
“…The BC participants in the current imaging study were drawn from the survivor cohort from the studies reported by Yamada et al (2010) and Nguyen et al (2013), and healthy controls were drawn from a study examining changes in decision-making across the adult lifespan (Denburg et al, 2007). A more complete description of the recruitment procedures are discussed in these references.…”
Section: Subjectsmentioning
confidence: 99%
“…Nguyen et al . () reported on the final sample of N = 87 subjects subdivided into individuals receiving chemotherapy, local therapy only and non‐cancer controls. Significant differences were seen between the groups for the MMSE, Letter‐Number Sequencing, Wisconsin Card Sorting Tasks and TMT, Part A with the BC survivors scoring lower even after controlling for age, education, and medical comorbidity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations